Effect of Lactobacillus acidophilus on Haematological Parameters of Murrah Buffalo Calves - Ojha, Lamella; Kumar, Sachin; Kewalramani, Neelam; singh, Abhishek kumar; Sarkar, Srobana; Tyagi, Amrish Kumar (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to evaluate the impact of Lactobacillus acidophilus on haematological parameters of Murrah buffalo Calves. Twenty four neonatal calves (5-7 days) were divided into four groups of six calves each. The calves were assigned to different dietary treatments viz. CON (basal diet alone, control), T1 (basal diet+ as a fermented milk @ 100 mL/calf/day having 108 CFU/mL), T2 (basal diet+ as a fermented milk @200 mL/calf/day having 108 CFU/mL) and T3 (basal diet+ as a fermented milk 300 mL/calf/day having 108 CFU/mL) for a period of 90 days. Significant weight gain was observed in probiotic supplemented group. The average dry matter intake was also highest (P<0.05) in T2, T3 compared to CON while the value for T1 was comparable to T2, T3 and CON. The results showed that there was a significant increase in leucocyte count in T2, and T3 group as compared to control and T1group. There was no effect (P>0.05) of the supplementation of probiotic on Haemoglobin, Total Erythrocyte Count and Packed Cell Volume. Mean Corpuscular Volume in T2 and T3 supplemented groups showed significantly higher values as compared to control and T1 group. Â Significantly higher values of Mean Corpuscular Haemoglobin and Mean Corpuscular Haemoglobin Concentration were observed in T1, T2 and T3 group than control group. There was no significant difference observed between the different groups throughout the experimental study in Neutrophils (%), Lymphocytes (%), Monocytes(%), Eiosinophils (%) andÂ Basophil(%).It may therefore be concluded that supplementation of probiotic as Lactobacillus acidophilus is advantageous in improving leucocyte count, Mean corpuscular volume, Mean corpuscular haemoglobin and Mean corpuscular haemoglobin concentration in Murrah buffalo calves however, the observed responses among the treatment groups were more evident in T2 and T3 fed groups compared to CON.